The role of Medical Director: obligations and responsabilities in a pediatric hospital. - D. Galante (Pediatric Anesthesia and Critical Care Journal (PACCJ))
The medical director in a pediatric hospital plays a crucial role in ensuring that the hospital provides high-quality healthcare services, complies with relevant laws and reg- ulations, and promotes an environment of safety for pa- tients, families, and staff. In Italy, where pediatric healthcare faces both unique challenges and distinct legal frameworks, the responsibilities of the medical director (or “Direttore Sanitario”) are particularly complex. This article explores the various obligations and responsibili- ties of the medical director in a pediatric hospital, with a focus on the balance between legal duties and clinical management.